Micotoxinas, características nutricionais e rendimento de grãos de híbridos de milho de segunda safra em ambientes e épocas de semeadura - Madalosso , Tiago (2024)
Corn is the main component in the production of animal feed. Gains in grain yield have been increased by genetic improvement of hybrids, however, little focus has been given to nutritional characteristics and resistance to toxin-producing fungi. The objective of this work was to evaluate the concentration of mycotoxins, grain yield and nutritional characteristics of twenty corn hybrids cultivated in the second harvest. The experiments were planned in the 2020 and 2021 harvests in the municipality of Cafelândia-PR. In addition to productivity, biometric characteristics and grain yield components were determined in the field. After harvesting, the levels of aflatoxins, fumonisins, zearalenone and deoxynivalenol were determined using highperformance liquid chromatography coupled to mass spectrophotometry, in addition to the levels of crude protein, starch and ether extract using near-infrared spectroscopy. Both harvests were marked by harmful environmental conditions, with low occurrence mainly during the corn reproductive period. The hybrids with the highest grain yield on average across the experiments were MG 593 and DKB 255, with the component that best explained grain yield being the mass of one thousand grains. The environmental conditions during the experiment were unfavorable to the production of toxins in corn grains. Fumonisins were the toxins detected in greater frequency and concentration. The hybrids AG 9000, DKB 255, DKB 360 and P3380 showed the highest concentration of fumonisins and MG30A37 the highest levels of zearalenone and deoxynivalenol. Within the group of sensitive hybrids, the occurrence of toxins in greater or lesser concentrations depends on the environment. The MG 593 hybrid was the one that presented the best composition of indicators, with high grain yield, low protein production and adequate levels for protein, starch and fats.